Sri Lanka, peace without process - Raman, B.; Sathiya Moorthy, N.; Chittaranjan, Kalpana; Observer Research Foundation. Chennai Chapter (Colombo 4 : Vijitha Yapa Pub., 2006)
Contributed articles presented at a seminar organized by Chennai Chapter of Observer Research Foundation on 27 September 2003 on ethnic conflict and peace-building exercises in Sri Lanka post 1978.
Includes bibliographical references and index.
Keywords: Ethnic conflict -- Sri Lanka -- Congresses; Peace-building -- Sri Lanka -- Congresses; Conflict management -- Sri Lanka -- Congresses; Sri Lanka -- Politics and government -- 1978- -- Congresses